Postpartum practices of puerperal women and their influencing factors in three regions of Hubei, China - Liu, Nian (BioMed Central, 2006)
BACKGROUND: 'Sitting month' is a Chinese tradition for women's postpartum custom. The present study aims to explore the postpartum dietary and health practices of puerperal women and identify their influential factors in three selected regions of Hubei, China. METHODS: A cross-sectional retrospective study was conducted in the selected urban, suburban and rural areas in the province of Hubei from 1 March to 30 May 2003. A total of 2100 women who had given birth to full-term singleton infants in the past two years were selected as the participants. Data regarding postpartum practices and potentially related factors were collected through questionnaire by trained investigators. RESULTS: During the puerperium, 18% of the participants never ate vegetables, 78.8% never ate fruit and 75.7% never drank milk. Behaviour taboos such as no bathing, no hair washing or teeth brushing were still popular among the participants. About half of the women didn't get out of the bed two days after giving birth. The average time they stayed in bed during this period was 18.0 h. One third of them didn't have any outdoor activities in that time periods. The educational background of both women and their spouses, location of their residence, family income, postnatal visit, nutrition and health care educational courses were found to be the influencing factors of women's postpartum practices. CONCLUSION: Traditional postpartum dietary and health behaviours were still popular among women in Hubei. Identifying the factors associated with traditional postpartum practices is critical to develop better targeting health education programs. Updated Information regarding postpartum dietary and health practices should be disseminated to women.